2019
DOI: 10.1039/c9ra03896e
|View full text |Cite
|
Sign up to set email alerts
|

Subtle chemical modification for enrichment of Fmoc-amino acid at a phospholipid interface

Abstract: A modest chemical modification of the Fmoc-amino acids led to enhanced interaction with a model surface for biomembrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Gour et al reported the self-assembly of the nonaromatic amino acids cysteine (Cys) and methionine (Met) into amyloid-like fibrils in neutral water . The formation of amyloid-like assembled structures was verified by binding assays of Thioflavin T (ThT) and Congo red (CR) as ThT exhibited significant fluorescence enhancement, while CR showed increased red-shifted light absorption intensity upon binding to the amyloid structures. , In addition, amino acids could self-assemble into 3D gels through molecular modification. , Typically, Fmoc-modified amino acids are able to trap solvent molecules to form hydrogels. , Among these, as a leading hydrogel promoter, Fmoc-Phe has excellent assembly capabilities and could self-assemble into efficient, stable, and transparent hydrogels with a minimum gelation concentration of 0.1% w/v. Hydrogels with 3D structures act as templates to complex with silver ions (Ag + ) and induce the formation of silver nanoclusters in the presence of diffuse sunlight at pH 7.46 and room temperature .…”
Section: Assembly Mechanism Of Amino Acid Based Materialsmentioning
confidence: 99%
“…Gour et al reported the self-assembly of the nonaromatic amino acids cysteine (Cys) and methionine (Met) into amyloid-like fibrils in neutral water . The formation of amyloid-like assembled structures was verified by binding assays of Thioflavin T (ThT) and Congo red (CR) as ThT exhibited significant fluorescence enhancement, while CR showed increased red-shifted light absorption intensity upon binding to the amyloid structures. , In addition, amino acids could self-assemble into 3D gels through molecular modification. , Typically, Fmoc-modified amino acids are able to trap solvent molecules to form hydrogels. , Among these, as a leading hydrogel promoter, Fmoc-Phe has excellent assembly capabilities and could self-assemble into efficient, stable, and transparent hydrogels with a minimum gelation concentration of 0.1% w/v. Hydrogels with 3D structures act as templates to complex with silver ions (Ag + ) and induce the formation of silver nanoclusters in the presence of diffuse sunlight at pH 7.46 and room temperature .…”
Section: Assembly Mechanism Of Amino Acid Based Materialsmentioning
confidence: 99%